2015
DOI: 10.1021/acs.jpcc.5b03580
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Shape-Controlled Synthesis of Pd Concave-Disdyakis Triacontahedra in Deep Eutectic Solvent

Abstract: Concave-disdyakis triacontahedral palladium nanocrystals (C-DTH Pd NCs) bound with 120 {631} high-index facets were prepared by electrochemically shape-controlled method in deep eutectic solvent (DES). It has found that both the adsorption of urea derived from EDS and the upper (E U ) and lower (E L ) limit potentials of the square-wave potential applied in the synthesis are contributed synergetically in controlling the shape of Pd NCs. The formation of C-DTH Pd NCs with well-defined shape was achieved by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 73 publications
1
43
0
Order By: Relevance
“…Pd nanoparticles with HIFs have also been reported in the past literature, including concave nanocubes, concave disdyakis triacontahedra (C‐DTH), concave tetrahedra, concave nanocubes, and arrow‐headed tripods . Pd concave nanocubes enclosed by {730} facets were previously synthesized by Xie et al through a one‐pot liquid method.…”
Section: D To 2d Pd Nanoarchitecturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pd nanoparticles with HIFs have also been reported in the past literature, including concave nanocubes, concave disdyakis triacontahedra (C‐DTH), concave tetrahedra, concave nanocubes, and arrow‐headed tripods . Pd concave nanocubes enclosed by {730} facets were previously synthesized by Xie et al through a one‐pot liquid method.…”
Section: D To 2d Pd Nanoarchitecturesmentioning
confidence: 99%
“…C‐DTH Pd NCs enclosed with {631} facets were prepared through electrochemical deposition on a working electrode from a deep eutectic solvent . The time‐dependent experiments revealed that the unique C‐DTH structure was evolved from octahedral and icosahedral structures ( Figure ).…”
Section: D To 2d Pd Nanoarchitecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic performance of Pd nanoparticles can be optimized by adjusting their size and morphology, therefore reducing the amount of this noble metal catalyst in various catalytic reactions as much as possible. Recently, significant progress has been made, using various methods, for shape-controlled syntheses of Pd nanoparticles, such as cube, octahedron, dodecahedron, concave, flake, rod, and linear Pd nanoparticles [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Among the methods used to create shape-controlled syntheses of precious metal nanoparticles, one efficient strategy includes the introduction of small adsorbents, such as halogen ions, to selectively adsorb on specific crystal planes to change crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Nanostructures with stepped facets exhibit relatively high activity, compared with commonly observed nanostructures. 16 Therefore, they could be optimal catalysts. Thus, much effort has been dedicated to developing new technologies for preparing Pd-based nanostructures with stepped facets.…”
Section: Introductionmentioning
confidence: 99%